Pleiotropic mechanisms of action of lenalidomide efficacy in del(5q) myelodysplastic syndromes. Issue 10 (October 2010) - Heise, Carla; Carter, Troy; Schafer, Peter; Chopra, Rajesh
Lenalidomide has demonstrated clinical activity in myelodysplastic syndromes, particularly in patients with a deletion in the long arm of chromosome 5 (del[5q] abnormality). It has a direct effect on the del(5q) clone, which may contribute to its ability to induce cytogenetic responses. Lenalidomide also stimulates erythropoiesis, leading to erythroid responses in certain patients. Other effects include immunomodulation, anti-inflammatory effects and angiogenesis inhibition. New findings indicate that lenalidomide modulates key genes located within the del(5q) region, including tumor suppressor genes, and regulators of the actin cytoskeleton and cell membrane. Its effects on cytoskeleton regulation may explain its direct antitumor and immunomodulatory effects. This article provides an overview of the known effects of lenalidomide and new insights into its activity in del(5q) myelodysplastic syndromes.